DRUG-INDUCED QT PROLONGATION - Жамба, А.О. (World of Medicine and Biology, 2015)
Introduction. Drug induced QT prolongation at the ECG and development of life-threatening polymorphic ventricular tachyarrhythmias (torsades de pointes) and sudden death in this background began to acquire significance like serious medical problem. There are many reports in literature that the QTs prolongation is quite common adverse reactions of drugs of different pharmacological groups. The aim of this study was demonstration of the QT prolongation problem, caused by the use of non-cardiac groups of drugs. Main part. In practical cardiology been achieved consensus that increase of corrected QT interval over 440 msec at ECG at rest indicates QT interval prolongation. An increase of QTc on 30-60 msec in patients taking the new drug should cause suspicion about a possible connection with the drug. The increase in absolute QTc duration over 500 msec and a relative increase of more than 60 msec should be seen as a marker of risk of ventricular tachycardia type torsades de pointes. The degree of dispersion of the interval QT, which is critical for arrhythmogenic drug action, varies within 80-120 ms. The article demonstrates the issue of diagnosis, risk factors for QT prolongation during treatment with drugs. Mechanisms and the list of drugs that induce QT prolongation, including antiarrhythmic drugs, antibiotics like macrolides and fluorchinolones, antihistamines, antidepressants, neuroleptics, antimalarial, antifungal, antiviral, antihypertensive and other groups specified in the article. It was established that the mechanism of severe cardiotoxic reactions associated mainly with the blockade of the gene of HERG (human ether a-go-go-related gene), which regulates the flow of ions through potassium channels IKr. The risk of cardiotoxic reactions increases at drugs overdose, dysfunction of organs involved in their metabolism and / or excretion, and because of drug interactions. QT interval prolongation may occur at electrolyte disturbances such as hypokalemia, hypocalcaemia, hypomagnesaemia. The methods of prevention, monitoring, accounting of interval QT prolongation proposed. So, to prevent drug-induced QTs prolongation is recommended: do not exceed therapeutic dose; correct the dosage of drugs to patients with heart disease and other risk factors; avoid simultaneous use of drugs that slow down their metabolism, excretion, prolonging QTs or cause hypokalemia; monitor ECG and potassium levels before and during treatment. Using the drug that can prolong QTs, it is desirable to provide the patient with written information about all risk factors. List of drugs that can prolong QTs is proposed to publish at national directories of drugs. Regular ECG monitoring before and during treatment for early diagnosis of possible interval QT prolongation is recommended. In order to compose a database of drugs, the use of which is associated with the risk of life-threatening arrhythmias, should create special pages on medical websites. Conclusions: There are difficult tasks before a doctor of the correct drug choice from a huge number of drugs on the criteria of efficiency and safety. Proper monitoring the QT interval will avoid serious cardiovascular complications. So, regular ECG monitoring before and during treatment for early diagnosis of possible QT prolongation and its dispersion be advised.